Pemberdayaan Kader Posyandu Dalam Stimulasi Deteksi dan Intervensi Dini Sikumbang (Psikologi,Tumbuh, Kembang) Anak - Liyanovitasari; Natalia Devi Oktarina; Swantika Ilham Prahesti (UNIVERSITAS NGUDI WALUYO, 2023)
Toddler Growth and Development Detection (DTKB) and detection of children's psychological health is very important to be carried out routinely and continuously because developmental abnormalities that are detected early will get appropriate interventions so that it will increase the success of the interventions given. The role of cadres needs to be increased to stimulate early detection and early intervention of developmental deviations. This activity aims to increase the knowledge and skills of cadres in stimulating early detection and intervention (psychological health, growth, and development), so that they are able to find early deviations in child growth and development. This community service activity wascarried out for 1 day on August 3rd 2022 which started with three stages, namely first providing counseling using the lecture method about growth, development and psychological health of children which begins with a pre test. Both simulations of growth measurements (weight, height, head circumference, arm circumference), measurements of children's development using the Developmental Pre-Screening Questionnaire (KPSP), and measurements of children's psychological health. The three stages of evaluation are with a post test and observation of cadre skills. Participants in the activity were 8 Strawberry Cadres at the RW 5 meeting hall in Gedanganak Ungaran Timur Village. The evaluation resultsshowed that 100% of participants' knowledge increased and 75% of participants' abilities increased and allparticipants were very enthusiastic and had high motivation to carry out early detection of children's development and psychology. In addition, the activeness of the participants was seen from their 100% attendance and enthusiasm when the counseling was given. It is hoped that this activity can increase the knowledge of cadres' abilities in carrying out early detection of child growth and development and are ableto know the psychological health of children which so far has received little attention. ABSTRAK Deteksi Tumbuh Kembang Balita (DTKB) dan deteksi kesehatan psikologis anak sangat penting dilakukan secara rutin dan berkelanjutan karena kelainan tumbuh kembang yang dideteksi secara dini akan mendapatkan intervensi yang sesuai sehingga akan meningkatkan keberhasilan intervensi yang diberikan. Peran kader perlu ditingkatkan untuk stimulasi deteksi dini dan intervensi penyimpangan perkembangan secara dini. Kegiatan ini bertujuan untuk meningkatkan pengetahuan dan ketrampilan kader dalam stimulasi deteksi dini dan intervensi (kesehatan psikologi, tumbuh, kembang), sehingga mampu menemukan penyimpangan dini tumbuh kembang pada anak. Kegiatan pengabdian masyarakat ini dilakukan selama 1 hari pada tanggal 3 Agustus 2022 yang dimulai ini terdapat tiga tahapan yakni pertama pemberian penyuluhan dengan metode ceramah tentang pertumbuhan, perkembangan, dan kesehatan psikologis anak dimana diawali dengan pre test. Kedua simulasi pengukuran pertumbuhan (BB, TB, lingkar kepala, lingkar lengan), pengukuran perkembangan anak menggunakan Kuesioner Pra Skrining Perkembangan (KPSP), dan pengukuran kesehatan psikologis anak. Ketiga tahapevaluasi dengan post test dan observasi keterampilan kader. Peserta kegiatan adalah Kader Strawberry berjumlah 8 orang di balai pertemuan RW 5 Desa Gedanganak Ungaran Timur. Hasil evaluasi menunjukkan 100% pengetahuan peserta meningkat dan 75% kemampuan peserta meningkat serta semua peserta sangat antusias dan memiliki motivasi tinggi untuk melakukan deteksi dini tumbuh kembang dan psikologis anak. Selain itu keaktifan dari peserta terlihat dari kehadiran 100% dan antusias saat penyuluhan diberikan. Diharapkan kegiatan ini dapat meningkatkan pengetahuan kemampuan kader dalam melakukan deteksi dini tumbuh kembang anak dan mampu mengetahui kesehatan psikologis anak yang selama ini masih kurang diperhatikan.